Searching for the silver linings of techno-invasion - Heike Diller; Stephen Jeffrey; Marina Fiedler (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2016)
Current research has established a clear negative impact of technological sources of stress on work-related outcomes. This study proposes that the invasion of technology into the private sphere is not always perceived negatively by individuals per se. The authors used structural equation modeling with a sample of 479 employees in Germany to test whether techno-invasion (technology invading personal life) can lead to emotional exhaustion as well as eustress (positive stress). In doing so, we advance our understanding of the dual effects technology has on an individual's life. The study further examines to what extent individuals themselves and their resources are responsible for the effects of technological stressors on stress responses. Our empirical results confirm that techno-invasion increases both positive and negative stress responses. Individual resources as mediators are shown to play a key role in the stressor-response relationship. Unexpectedly, the six tested resources do not have similar effects on stress responses. The authors discuss practical implications and future research directions.
Keywords: 650; techno-invasion; stress responses; emotional exhaustion; eustress; resources